ANALYSIS OF COMPARATIVE INDICATORS OF PRODUCTION PRODUCTION TRENDS IN DEHKAN FARMS AND HOUSEHOLDS - Ochilova, Nargiza Akramovna (THE INNOVATION ECONOMY, 2024)
This article examines the share of agricultural products grown on farms in the Kashkadarya region by district, the share of farmers and farmsteads in the main food products grown and the dynamics of productivity indicators, production in individual farms and household plots, and an analysis of the indicators.